Hot tea and tiny tots don't mix: A cross-sectional survey on hot beverage scalds. Issue 8 (December 2017) - Burgess, J.D.; Kimble, R.M.; Watt, K.A.; Cameron, C.M.
Highlights: Being proximally close to a young child does not equate to adequate supervision as injuries still occur. Attentiveness and continuity of supervision may be more effective in reducing childhood injury risk. The peak in hot beverage scald prevalence is closely associated with an infants developmental changes, particularly mobility. Non-primary caregivers can be caught off-guard by a young child's rapid changes in mobility. Parents and caregivers of young children are largely unaware of correct burn first aid treatment. Abstract: Objective: Hot beverage scalds are a leading cause of burns in young children. The aim of this study was to look at the circumstances surrounding these injuries in terms of setting, mechanism, supervision and first aid to inform a prevention campaign. Methods: A cross-sectional study was delivered via iPad to parents and caregivers presenting with a child aged 0–36 months with a hot beverage scald at a major paediatric burns centre. Results: Of the 101 children aged 0–36 months that presented with a hot beverage scald over a 12-month period, 54 participants were included. The scald aetiology was as expected with the peak prevalence in children aged 6–24 months, pulling a cup of hot liquid down over themselves. The majority of injuries occurred in the child's home and were witnessed by the caregiver or parent. The supervising adult was often in close proximity when the scald occurred. Less than a third (28%) of participants received recommended first aid treatment at the scene, with an additional 18% receiving this treatment with three hours of the injury—usually at an emergency department. Conclusions: While the aetiology of these scalds were as expected, the low use of recommended burn first aid was of concern. Although supervision was present in almost all cases, with the parent/caregiver close-by, this proximity still permitted injury. Attentiveness and continuity of supervision, which can be difficult with competing parental demands, appear to play a more important role role; as do considerations of other safety mechanisms such as hazard reduction through keeping hot drinks out of reach and engineering factors such as improved cup design. By incorporating the findings from this study and other research into a hot beverage scald prevention campaign, we hope to see a change in knowledge and behaviour in parents and caregivers of young children, and ultimately a reduction in the incidence of hot beverage scalds.